PENGARUH PERSAINGAN AUDITOR DAN SIFAT MACHIAVELLIAN PADA INDEPENDENSI AUDITOR DENGAN ETIKA PROFESI SEBAGAI VARIABEL MODERASI - Mahayani, Ni Putu Eka; Merkusiwati, Ni K. Lely Aryani (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
This study is an empirical study to test the effect of competition variable Machiavellian nature of the auditor and auditor independence with the ethics of the profession as a moderating variable. Data collection method used is using questionnaires distributed directly to the auditor who works in Bali. The population in this study were all auditors working in the public accounting firm in Bali with the overall number of auditors as many as 70 people. The samples used were 67 Auditor with purposive sampling method. The analysis technique used is Moderated Regression Analysis (MRA). Based on the analysis and hypothesis testing, it could be concluded that (1) the competition auditor negative effect on the independence of the auditor, (2) the nature of Machiavellian negative effect on the independence of auditors, (3) professional ethics moderate (weaken) the effect of competition auditor to auditor independence, (4 ) professional ethics moderate (weaken) the effect of the Machiavellian nature of the auditor's independence.
Keywords: Competition Auditor, Machiavellian nature, Auditor Independence, Professional Ethics